Capital structure and profitability: a study of listed manufacturing companies in sri lanka - Shanthini, G.; Velnampy, T. (university of Jaffna, 2014)
The successful selection and use of capital is one of the key elements of the firms' financial strategy. Capital structure is the composition of debt and equity capital of the firm. Therefore proper care and attention need to be given to determine capital structure decision. The purpose of this study is to analyse the capital structure and profitability of listed manufacturing companies in Sri Lanka over the past 10 year period from 2003 to 2012. The data have been analyzed by using descriptive statistics, correlation and regression analysis. The results show that Debt to Equity ratio (D/E) is negatively associated with the profitability ratios [Gross Profit Ratio (GPR); and Net Profit Ratio (NPR)] except Return on Equity (ROE) and Return on Asset (ROA). Further capital structure has a impact on all profitability ratios The outcomes of the study may guide entrepreneurs, loan- creditors and policy planners to formulate better policy decisions in respect of the mix of debt and equity capital and to exercise control over capital structure planning .
Keywords: Capital structure; Manufacturing company profitability